Antihypertensive and Diuretic Effects of The Ethanol Extract of Colocasia esculenta (L.) Schott. Leaves - RINI PRASTIWI; SISKA SISKA; ERVINA BHAKTI UTAMI; GIGIH PANGESTU WITJI (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
Colocasia esculenta (L.) Schott (CE) is traditionally used for the treatment of various ailments such as high blood pressure, diarrhea, rheumatic pain, pulmonary congestion, etc. Hence in present study, the effect of ethanol extract of CE leaves (EECE) was evaluated for antihypertensive and diuretic activity in rats. Male Sprague dawley rats were randomly divided into five groups (n=5), and treated as follow: positive control group (hydrochlortiazide 0.2569 mg/ 200 g bw), negative control (NaCl 8%) and EECE (20, 40 and 80 mg/ 200 g bw) was given 14 days. The parameters systole blood pressure (SBP) and diastole blood pressure (DBP) was estimate by Kent Scientific’s CODA Non-invasive Blood Pressure on the days 0, 15 and 29. Diuretic activity of EECE was studied based on the volume of urine for 6 hours and measuring the levels of sodium in urine 24 hours. The result of the study showed that EECE 40 mg/ 200 g bw/ day significant (p<0.05) decreased in SBP 16.07% and in DBP 13.67%. EECE 40 mg/ 200 g bw/day showed positive diuretic activity and significantly (p < 0.05) increased sodium levels in urine. Preliminary phytochemical evaluation revealed the presence of saponins, tannin, triterpenoid and flavonoids in EECE.